Structural and compositional analyses of Cu(In,Ga)Se-2 thin film solar cells with different cell performances - Kim, Minjung; Lee, Jihye; Lee, Yeonhee; Jeong, Jeung-hyun; Lee, Kang-Bong (A V S AMER INST PHYSICS, 2016)
Copper indium gallium selenide (CIGS) absorber thin films were deposited on bilayer Mo back contacts with and without a SiOx film on a soda-lime glass substrate. This was done to control the quantity of alkali metals in the films and to apply the growth method to a substrate that does not contain alkaline elements. The average concentrations of major elements Cu, In, Ga, and Se in the CIGS solar cells were measured by electron probe microanalysis, secondary ion mass spectrometry (SIMS), and Auger electron spectrometry. The SIMS technique was also used to obtain and compare depth profiles of the relative ion intensities of sodium and potassium alkali metals for CIGS thin films with varying cell efficiencies. The CIGS/Mo interfaces also were investigated by transmission electron microscopy (TEM), whereby a cross-sectional view of Mo films prepared with and without an initial SiOx layer made possible the detection of a MoSe2/Mo bilayer with a columnar-type microstructure. Scanning TEM images and corresponding elemental maps via energy-dispersive x-ray spectra and high-resolution TEM images revealed the clear formation and orientation of a MoSe2 layer between the CIGS and Mo layers. The solar cell sample exhibiting high efficiency had a thick well-oriented MoSe2 layer at the CIGS/Mo interface, in contrast to the cell sample exhibiting low efficiency. (C) 2016 American Vacuum Society.
Keywords: HIGH-EFFICIENCY; QUANTITATIVE-ANALYSIS; ICP-OES; MOSE2; GROWTH; NAF